IMPLEMENTASI PERATURAN OTORITAS JASA KEUANGAN NOMOR: 3/POJK.03/2016 TENTANG PENERAPAN KEPATUHAN SYARIAH PADA PT. BPRS PUDUARTA INSANI - Gaspari, Andrian (Al-Muhtarifin: Islamic Banking and Islamic Economic Journal, 2024)
The purpose of this study is to describe murabahah financing for business capital, the constraints and problems encountered, whether or not they comply with the implementation of financial services authority regulations: 3/POJK.03/2016 concerning the implementation of sharia compliance and supervision and DPS duties in BPRS puduarta Insani. Method the research used by the author is a qualitative approach. Qualitative research is a research method used to research on natural object conditions where the researcher is a key instrument, data collection techniques are carried out in a triangulation (combined) manner, data analysis is inductive in nature, and the results of qualitative research emphasize more meaning of generalization. This qualitative research is a research procedure that produces descriptive data in the form of written words from the results of interviews, observations, literature studies, and documentation.The results of the study show that the BPRS Puduarta Insani in general is in accordance with sharia principles and the provisions of the DSN-MUI Fatwa and the OJK. Which has been directly supervised by the DPS. From the submission mechanism to the signing of the contract, it is in accordance with sharia principles and it is also explained in detail how the mechanism for carrying out the business and installments until the completion of the financing so that there is no longer any attachment to the bank. In selecting customers, the bank also applies the precautionary principle by applying the 5C principle. Therefore BPRS Puarta Insani should comply with sharia principles and the principle of prudence in its activities. DPS also works according to its authority in supervising BPRS and providing advice and advice to BPRS, but the public still thinks that Islamic banks are the same as conventional banks, even though the problems they encounter often occur due to bad customer characteristics.Keywords: Implementation of Sharia Compliance and Murabahah